The Derodontidae, Dermestidae, Bostrichidae, and Anobiidae of the Maritime Provinces of Canada (Coleoptera: Bostrichiformia) - Majka, Christopher G. (Zootaxa, 2007)
The beetle families of the Bostrichiformia—the Derodontidae, Dermestidae, Bostrichidae, and Anobiidae – in the Maritime Provinces of Canada are surveyed. Seventy-four native and established introduced species are now known to occur including 30 found in New Brunswick, 65 in Nova Scotia, and 29 on Prince Edward Island. Seven species are newly recorded from New Brunswick, 24 from Prince Edward Island, and 37 from Nova Scotia for a total of 68 new provincial records. A total of 31 species are newly recorded in the Maritime Provinces as a whole, three of which, Dinoderus minutus (Fabricius), Ernobius filicornis LeConte, and Ernobius granulatus LeConte, are newly recorded in Canada. Two species, Ptilinus pruinosus Casey and Caenocara oculata (Say), are removed from the faunal list of New Brunswick, and one subspecies, Attagenus unicolor unicolor (Brahm), is removed from the faunal list of Prince Edward Island since no specimens or published records could be found to support their presence. Additional records of six other exotic species intercepted at ports and points in the region, but not established here, are also reported. A specimen of the Palearctic Ptinus bicinctus Sturm collected in 1915 in Nova Scotia, establishes a new early timeline for this species in North America. The fauna of the region is distinguished by the very large proportion (37 of 74 species, i.e. 50%) of which is introduced. It is also distinguished by the large proportion (22 of 37 species, i.e. 60%) of the indigenous, native fauna that is apparently rare, perhaps as a result of the historical impact of forest management practices on these wood-boring, saproxylic species. The fauna is further evaluated from both zoogeographic and ecological perspectives.